Patient-centred and not disease-focused : a review of guidelines and multimorbidity - Ong, Kim Yao (2021)
Introduction: Single-disease clinical practice guidelines (CPGs) are not designed to consider patients with multiple chronic conditions, or multimorbidity. Applying multiple CPGs to a single patient may create an overwhelming treatment burden resulting in poor adherence and clinical outcomes. No studies on the cumulative treatment burden from multiple CPGs have been done in Singapore. We described the treatment burden on a hypothetical patient with six chronic conditions when multiple CPGs were applied, and appraised each CPG with respect to the patient-centred care of older adults with multimorbidity. Methods: A treatment plan was developed for a hypothetical 72-year-old woman with asthma, depression, diabetes mellitus, dyslipidaemia, hypertension and osteoarthritis according to the latest CPG recommendations. Treatment burden was quantified in terms of time spent, cost, and the number of appointments and medications. Each CPG was appraised with respect to the care of older adults, patients with multimorbidity and patient-centred care. Results: Following the CPGs strictly, an average of about two hours was spent daily taking 14 different medications and following 21 non-pharmacological recommendations. Her out-of-pocket payment was SGD 104.42 monthly despite a near 90% subsidy on healthcare bills. Patient-centred care of older adults with multimorbidity was inadequately addressed in all six CPGs. Conclusion: When six CPGs were cumulatively followed, the treatment burden was time-consuming, costly and disruptive. Patients' goals and preferences must guide prioritisation of care such that treatment burden remains minimally disruptive to their lives. Developing future CPGs to deliver patient-centred rather than disease-focused care will be crucial to the management of multimorbidity.